Development of ground dune sand blended cement - Hassan, Omer Abdalla Alawad (2014)
Pozzolan materials (e.g. fly ash, slag, silica fume, rice husk ash) have been used successfully as a partial ordinary Portland cement (OPC) replacement material. However, there are some technical and economic drawbacks associated with the use of the existing pozzolan materials. Therefore, there is a growing interest to find an alternative material to be used as a source of siliceous materials for concrete production. This research aims to determine the potential of using ground dune sand (GDS) as partial cement replacement in binary (OPC-GDS) and ternary combinations of OPC-GDSslag and OPC-GDS-lime. The proposed combinations of blended cement system are expected to save large amounts of OPC. The primary objective of this study is to develop naturally available dune sand as an effective partial cementing material for use in the concrete industry. To achieve this objective, different treatment methods, namely, mechanical, chemical and thermal methods (autoclave curing) have been applied to determine the reactivity of GDS. For the ternary blended combinations, low (15%), moderate (30%) and high (45%) amounts of slag or lime were incorporated into a binder system containing 40% of GDS. Compressive strength, drying shrinkage and durability properties of the cast mixtures were investigated. Moreover, microstructure analyses were carried out using SEM, EDX, XRD, DTA and TGA analyses to characterize the hydrated products. A correlation between CaO/SiO2 and compressive strength was then carried out. The results revealed that autoclave curing is a promising curing system to utilize the GDS as partial cement replacement. The optimum level of replacement of OPC by GDS was found to be 30%, and up to 40% of GDS can be used without significant loss in the compressive strength. The inclusion of slag or lime as the ternary binder element to the mixture containing 40% of GDS yielded a compressive strength higher or comparable to the control mixture. The drying shrinkage and durability properties of blended autoclave cured mixes were significantly improved. The SEM, EDX, XRD, DTA and TGA analyses explained how GDS contributes to the strength and durability of blended mixtures. The outcome of this research will benefit the Middle East and other countries where supplies of natural dune sands are unlimited.